The religious traditions of Japan, 500-1600 - Bowring, Richard John 1947-; Frederick and Kazuko Harris Library Collection (Cambridge, UK Cambridge University Press, 2005)
"The Religious Traditions of Japan, 500-1600, describes in outline the development of Japanese religious thought and practice from the introduction of writing to the point at which medieval attitudes gave way to a distinctive pre-modern culture, a change that brought an end to the dominance of religious institutions. A wide range of approaches using the resources of art, history, social and intellectual history, as well as doctrine, is brought to bear on the subject. It attempts to give as full a picture as possible of the richness of the Japanese tradition as it succeeded in holding together on the one hand, Buddhism, with its sophisticated intellectual structures, and on the other hand the disparate local cults that eventually achieved a kind of unity under the rubric of Shinto. Much of this book is concerned with the way in which Buddhism used the local cults to consolidate its position of hegemony while at the same time offering an example against which Shinto could slowly invent itself. An understanding of this process of constant and at times difficult interaction is essential to a deeper appreciation of Japan's history and its cultural achievements."--BOOK JACKET.
pt. 1. The arrival of Buddhism and its effects (c. 538-800): The introduction of Buddhism -- Creating a dynasty -- Buddhism and the early state -- Monuments at Nara -- pt. 2. From Saichåo to the destruction of Tåodaiji (800-1180): The beginnings of a 'Japanese' Buddhism: Tendai -- The beginnings of a 'Japanese' Buddhism: Shingon -- Buddhism and the state of Heian Japan -- Shrine and state in Heian Japan -- The rise of devotionalism -- In a time of strife -- pt. 3. From the destruction of Tåodaiji to the fall of Go-Daigo (1180-1330): For and against exclusive practice of the nenbutsu -- Religious culture of the early 'middle ages' -- Chan Buddhism -- Zen Buddhism -- Reform from within and without -- The emergence of Shintåo -- Taking stock -- pt. 4. From the fall of Go-Daigo to the death of Nobunaga (1330-1582): Two rival courts -- Muromachi Zen -- The end of the medieval -- Appendices: Reading Shingon's two maònòdala.
Includes bibliographical references (p. 448-461) and index.
Keywords: Japan -- Religion -- To 1600.